2021
DOI: 10.3389/fped.2021.646923
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Renal Transplant Outcome in Patients With Posterior Urethral Valves. Prognostic Factors Related to Bladder Dysfunction Management

Abstract: Introduction: To obtain a successful renal transplant (RT) outcome in patients with posterior urethral valves (PUV), it is necessary to accomplish an adequate bladder dysfunction treatment. Our aim was to determine prognostic factors related to bladder dysfunction management in long-term RT outcome in patients with PUV.Methods: A retrospective review of patients with PUV who received a first RT after 1985 in our institution with at least 5 years of follow-up was performed. Variables analyzed included prenatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Most of their patients (10/12) were augmented with a ureter. Amesty et al recently conducted a review to determine prognostic factors related to managing bladder dysfunction in boys with PUV and a renal transplant but did not find any clear indication regarding the time of bladder augmentation in relation to the time of transplantation [ 19 ]. These findings are consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Most of their patients (10/12) were augmented with a ureter. Amesty et al recently conducted a review to determine prognostic factors related to managing bladder dysfunction in boys with PUV and a renal transplant but did not find any clear indication regarding the time of bladder augmentation in relation to the time of transplantation [ 19 ]. These findings are consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Neonates with LUTO have been shown to have significant bladder dysfunction (sometimes referred to as "valve bladder"), which is manifested by decreased bladder capacity and compliance with increased instability, and optimal bladder dysfunction management in neonates and children may even improve renal transplant outcomes in LUTO cases. 44,45 Tanaka et al demonstrated that a low pressurelimited valve system (15-54 mm Hg) can preserve fetal lamb bladder volume with reduction of both interstitial fibrosis and bladder muscle hypertrophy. 46 Our hope is that incorporating a one-way valve will allow bladder cycling and preservation of function.…”
Section: Discussionmentioning
confidence: 99%
“…Rigid management of bladder dysfunction should also be performed in PUV patients with renal transplantation. Two recent studies showed that patients with Mitrofanoff procedures or clean intermittent catheterizations had significantly better graft survival rates, which was also comparable to graft survival rates for other indications [ 64 , 65 ]. Unsurprisingly, the sonomorphologic hallmarks of hypodysplastic kidneys such as hyperechogenicity, low kidney volume and pathologic corticomedullary differentiation also are prognostic factors for the progression towards ESKD [ 47 ].…”
Section: Prognostic Factors For Chronic Kidney Disease Developmentmentioning
confidence: 90%
“…In a French multicenter study, Marchal et al found that even though enterocystoplasties and continent urinary diversions exposed grafts to more frequent acute graft pyelonephritis, patient and graft survival rates in lower urinary tract malformations at 10 years were similar to the survival rates of other kidney transplantations on native bladders [ 65 ]. Amesty et al recently showed that optimal bladder control using either clean intermittent catheterization or Mitrofanoff procedures resulted in more urinary tract infections, but prolonged graft survival [ 64 ]. It should therefore be mandatory to screen for and treat bladder dysfunction before renal transplantation, in order to prolong graft survival and ensure the optimal use of scarce transplant organs.…”
Section: Management Of Chronic Kidney Disease In Posterior Urethral V...mentioning
confidence: 99%